The glacial history of the Hans Tausen Iskappe and the last glaciations of Peary Land, North Greenland - Landvik, Jon Y.; Anker, Weidick; Hansen, Anette (Meddelelser om Grønland. Geoscience, 2001)
Studies of glacial geology near the Hans Tausen Iskappe, 82°N, suggest that the Greenland Ice Sheet covered Peary Land during the Late Weichselian. The ice sheet experienced successive marginal retreat due to calving along the major fjords, and an extensive thinning in response to the climatic amelioration during the early Holocene. Local ice caps had melted by ca. 8100 cal years ago, a result which is compatible with the studies of an ice core record from the Hans Tausen Iskappe. The present ice caps are thus not relicts from the Weichselian, but have formed during the Holocene. Findings of 5000-6000 year-old driftwood along fjords that connect to the Arctic Ocean indicate that the perennial sea-ice cover was gone during the mid-Holocene.